Síntese e caracterização dos vidros cálcio boroteluretos dopados com Sm2O3 - QUEIROZ , Maria Nayane de (2016)
The Sm2O3-doped calcium borotellurite glasses studied in this research were synthesized by melt-quenching method, characterized according to their structural, thermal, spectroscopic and optical properties and analyzed as a function of TeO2 concentration. The analysis of the properties was performed by the following characterizations: X-ray diffraction, volumetric density, Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), optical absorption spectroscopy, differential thermal analysis (DTA), specific heat, refractive index, photoluminescence and lifetime decay. In addition, molar volume, optical band gap, electronic polarizability, number of ions per cubic centimeter, interionic distance, chromaticity, DE/DM ratio and orange/red ratio values were also evaluated. The results have showed that the increase of TeO2 concentration increased the volumetric density (~41%). The X-Ray spectra confirmed the amorphous nature of the samples. The Raman and FTIR results indicated the presence of the following structures: TeO3, TeO3+1, TeO4, BO3 and BO4. Moreover, the increase of nonbridging oxygen was confirmed. The increase of the TeO2 concentration decreased the specific heat and the glass transition temperature of the samples. The refractive index increased, due to an increase of density and electronic polarizability. The insertion of the doping agent was confirmed by the optical absorption spectra, which presented peaks characteristic of Sm3+ ions (most intense peak at ~402 nm). The emission intensity of the Sm3+ ions decreased (~2.2%) with the increase of TeO2 concentration. The chromaticity of the samples analyzed by CIE diagram showed small variation at x and y positions. However, under visual inspection, the variation of the emitted color was not observed. The emission intensity as a function of temperature, showed a decrease for all samples. The lifetime for the emission at ~598 nm also presented a reduction with the increase of TeO2 content, due to the increase of NBOs. Therefore, the synthesized materials present good properties, and finds their applications as potential candidate for optical devices, such as solid state lasers, Light-emitting diodes (LEDs), among others.